Effects of the sustainable forestry Initiative on landscape function as measured by patterns of vertebrate habitats - Azevedo, João (2003)
The Sustainable Forestry Initiative (SFI) adopted in 1995 by the American Forest and Paper Association is currently applied over 90% of industrial forests in the US. This program has potential effects on forest landscape structure and function, including biodiversity. Here we analyze the effects of SFI application on the abundance and spatial pattern of vertebrate habitats in a 6,000-ha forested watershed in East Texas. Simulations of landscape structure changes in the study area were conducted based on forest inventory data and SFI rules such as regeneration harvest areas limits of 49 ha for pine and 12 ha for hardwoods, streamside management zones 30 m or more wide, and a three-year green-up interval. The 266 species (83 herps, 132 birds, 51 mammals) of vertebrates potentially occurring in the study area were grouped into 12 clusters based upon their habitat requirements. One species per cluster was selected as the indicator species for the cluster. Habitat Suitability Index models were used to develop habitat suitability maps for the indicator species based on the landscape simulations. Habitat abundance and spatial characteristics for individual vertebrate species were evaluated at different points of time to assess the effects of the SFI on vertebrate habitats as compared to reference scenarios.